Integrating nanopore sensors within microfluidic channel arrays using controlled breakdown1. Issue 6 (21st March 2015) - Tahvildari, Radin; Beamish, Eric; Tabard-Cossa, Vincent; Godin, Michel
<x xml:space="preserve">Abstract</x> Functional low-noise nanopore arrays are fabricated by controlled dielectric breakdown in solid-state membranes integrated within microfluidic devices.